The Design Argument: Hume's Critique of Poor Reason - Gaskin, John C. A. (Religious studies, 1976)
In an article in Philosophy (1968, pp. 199-211) R. G. Swinburne set out to argue that none of Hume's formal objections to the design argument have any validity against a carefully articulated version of the argument' (p. 199). This, he maintained, is largely because Hume's criticisms are bad criticisms of the argument in any form' (p. 206). The ensuing controversy between Swinburne and Olding1 has focused upon the acceptable/unacceptable aspects of the dualism presupposed in Swinburne's defence of the design argument; upon whether any simplification is achieved by reducing scientific explanation to agent explanation; and upon the problems which arise from taking a man's acting upon his body (or the material universe within his reach) as the analogy for understanding a disembodied agent acting upon matter. In this article I shall refer to the Swinburne-Olding controversy when appropriate but my main concern is to return to Swinburne's original article and argue, seriatim, that Hume's individual criticisms of the design argument are for the most part a great deal more powerful than Swinburne allowed. I shall contend that cumulatively they destroy the design argument as any sort of rational foundation for theistic belief. But first I shall indicate briefly the character of the argument together with one or two of the distinctions and refinements in terms of which it has been found helpful to carry on the discussion in recent years.